Kondycja finansowa Polaków i zadowolenie z życia po pandemii - Zbyrad, Teresa Jadwiga (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
The article aims to show the quality of life of Poles and their financial condition and level of satisfaction with life after the pandemic. The content of the paper revolves around issues related to quality of life, such as household budget, spending, life satisfaction and well-being, as well as fears and anxieties. The question that acquires relevance in this context is – What is the degree of satisfaction with life despite strained household budgets? What Poles can, and what they cannot, afford? What makes them happy and what arouses anxiety? A “diagnosis of life, attitudes, plans and aspirations of the Polish society” is offered and the results of the Public Opinion Research Center (CBOS) survey are discussed. The findings of the said survey show that the financial condition of Poles is not impressive, and most do not earn a high income, yet they can manage their current expenses. In addition, satisfaction with life is not declining and is driven by non-material values such as family, marriage and interpersonal relationships. Keywords: quality of life, income, financial condition, spending, satisfaction with life